(untitled) (Research, Society and Development, 2021)
Currently, the microbiological analysis is of extreme relevance in the food industry, because with it, it is possible to know the conditions under which the food was processed, the risks that it can offer to the final consumer, if the product has the desired useful life, besides to verify that microbiological standards for food standards are being followed properly. The present work aims to verify the sanitary quality of various foods from the presence of indicator microorganisms, such as mesophiles, total coliforms and thermotolerant coliforms, which indicate the possibility of fecal contamination. Among the foods analyzed, many were highly contaminated, pointing to poor sanitary conditions, making them unfit for consumption. Samples of sausage indicated an acceptable microbiological standard, not reaching high populations of mesophiles and coliforms that could disadvantage the product. This is no longer the case with the cheeses analyzed, since they were the most contaminated samples of the present project, reaching numbers greater than 107 NMP/g. With the work, it was possible to observe that costumers are subject to purchase a products considered to be unapproved for consumption and, unfortunately, in Brazil, there is not always a regulation that limits a maximum quantity of microorganisms indicators, thus not preventing the commercialization of foods contaminated, and can cause harm to the health of those who consume them. In order for such an act to be avoided at least, health authorities should act by better monitoring of products and guiding handlers on good sanitary practices.